Research on the GED Credential and Its Use in Wisconsin - (:unkn) unknown (My University, 1994)
In 1984 the Employment and Training Institute embarked on a two-year study of the GED and its use in Wisconsin, at the request of State Superintendent Herbert J. Grover. The study explored the use of the GED credential by employers and post-secondary institutions in the state, the level of skills attained by GED holders, and the performance of GED holders in post-secondary education in the state. Some of the findings of the research were positive, some were negative. The long-term goal of the research was to help insure that high school equivalency credentials issued in Wisconsin reflect the high school graduation standards of the state and deliver to adults who seek them an equivalency credential worthy of its name. Recommendations made by the Employment and Training Institute are aimed at strengthening the requirements for high school equivalency certificates in Wisconsin. The recommendation are intended to serve two purposes: to insure that adults earning the credential have acquired the basic skills they will need for employment and possible further education; and to insure that the level of educational attainment reached by most of the Wisconsin residents with GED credentials continues to be recognized as equivalent.
Keywords: GED; high school; truancy; Wisconsin